EMPLOYEE WELLBEING AND SUSTAINABLE WORKPLACE - Nadzrah Yusof; Salmi Mohd Isa; Goh Yen Nee (Journal of Islamic, Social, Economics and Development, 2022)
The concept of well-being in the context of one's place of employment is increasingly being brought up in mainstream organisational research. The focus of this paper is on the factors that are connected with one's well-being in their place of employment, and it also addresses two organising frameworks for the conceptualization of well-being at workplace. This paper aims to discuss the importance of employee wellbeing in creating a sustainable workplace. The paper draws on the various literature sources to create a conceptual model for employee wellbeing and sustainable workplace. Using the mini-review analysis it is found that the psychological factors significantly affect employee's well-being. Also, the employee's wellbeing has a significant effect on job performance. A major impact on an employee's overall well-being can be attributed to psychological variables. Additionally, the health and happiness of the worker has a substantial bearing on their performance at work